Using RegulonDB, the Escherichia coli K-12 gene regulatory transcriptional network database - Salgado, Heladia (Curr Protoc Bioinformatics, 2018)
In RegulonDB we have been gathering knowledge by manual curation from original scientific literature on the regulation of transcription initiation and the genome organization in transcription units of the Escherichia coli K-12 genome for over 25 years. This paper describes six basic protocols that can serve as a guiding introduction to the main content of the current version (v9.4) of this electronic resource. These include the general navigation as well as searching for specific objects such as genes, gene products, transcription units, promoters, transcription factors, coexpression, and Genetic sensory response units or GENSOR Units. Following the format of these protocols the user will find an initial introduction to the concepts pertinent to the protocol, what is the content when performing the given navigation, as well as the necessary resources. This easy to follow protocol shall help anyone interested to quickly see all what is currently offered in RegulonDB, including position weight matrices of transcription factors, coexpression values based on published microarrays, as well as the GENSOR Units unique to RegulonDB that offer regulatory mechanisms in the context of their signals and metabolic consequences.